Training On The Utilization Of Desktop Mendeley As A Reference Tool In Writing Scientific Papers For Teachers Of SMP Swasta Gita Surya Eban - Simarmata, Justin Eduardo; Dewi, Ni Putu Yuni Astriani; Sila, Vinsensia Ulia Rita; Sele, Yunawati; Shidik, Muhammad Amran (Talenta Publisher, 2021)
One of the software for compiling a bibliography automatically can take advantage of the facilities of the Mendeley Desktop application. Mendeley Desktop is a reference management software that helps organize scientific articles, namely in creating citations and bibliography. With this software, writers can manage reading sources that are used as references in compiling their writings. The use of Mendeley Desktop can also be integrated with Microsoft Word, so it can be more easily for writers for each scientific paper. The purpose of holding this training activity is to help the teachers of SMP Swasta Gita Surya Eban in order to utilize of the facilities provided by the software and the citations and references on the Mendeley Desktop so that scientific writing can be done more easily, quickly, and efficiently. From the training results, it was found that the training carried out could add knowledge and solutions to the use of Mendeley Desktop with the evaluation results increase significantly. The writers hope that by holding this training, teachers at SMP Swasta Gita Surya Eban can apply the citation / reference software from Mendeley Desktop in writing scientific papers.